Da Ṭal pah khwā keṣhe da s̲aqāfat rangūnah - Bangash, Salīm; Puṣhto Ikayḍīmī (Peṣhawar : Puṣhto Ikayḍīmī, Peṣhawar Yūnīwarsiṭī, 2018)
Historical and social cultural study of Pushtuns with special reference to Thal, Khyber Pakhtunkhw, Pakistan.
In Pushto.
Keywords: Pushtuns -- Pakistan -- Khyber Pakhtunkhwa -- History; Pushtuns -- Pakistan -- Khyber Pakhtunkhwa -- Social life and customs; Pushtuns -- Social life and customs; Pakistan -- Khyber Pakhtunkhwa; History